Morphological and anatomical investigation of three Scandix species from Turkey - Demirpolat, Azize; Dogan, Gulden; Bagci, Eyup (Bangladesh Botanical Society, 2019)
Morphological, morphometrical and anatomical features of some Scandix species (Scandix pecten-veneris, S. macrorhyncha and S. balansae) were investigated to compare and determine the taxonomic importance of these characters. Description, synonyms, Turkish names, flowering times, habitat properties and anatomical structure of each species were determined. According to morphological and anatomical characters S. macrorhyncha and S. pecten-veneris showed high-level similarity. However, endemic S. balansae showed distinct both morphological and anatomical differences from the other Scandix species. © 2019 Bangladesh Botanical Society. All Rights Reserved.
Keywords: Anatomy; Morphology; Scandix